Video Gim Sopan (Keselamatan Transportasi Jalan) untuk Siswa Sekolah Dasar - Yoga, Mahendra; Sugiyanto, Mohammad Ibrahim; Mohamad, Ar Rofiqi; Siswanto, Joko (Proceedings Series on Physical & Formal Sciences, 2023)
The behavior of motorized vehicle drivers who violate traffic rules is one of the most significant factors causing traffic accidents on the road. This is due to low traffic awareness. Low traffic awareness due to a lack of understanding of traffic rules. An Android-based polite game application was built to increase awareness of motorized vehicle drivers. Polite game development uses the waterfall method with supporting software such as Unity, Photoshop, and Visual Studio. Polite games can help you understand and be aware of the dangers that are on the road. The development of polite games can be done by adding game levels with other road safety theories.